The impacts of the COVID-19 crisis on the automotive sector in Central and Eastern European Countries - Klein, Caroline (OECD Economics Department Working Papers, 2021)
This paper aims at investigating the impact of the COVID-19 crisis on the automotive sector in Central and Eastern Europe. It details the effects of the pandemic and subsequent lockdown measures on the activity in the sector. It also discusses the prospects for car sales in the short to medium run, potential spillover effects in the region, and new risks to the supply chains posed by the pandemic. It shows that disruptions to the supply chains had limited impact so far and that the sector has been mainly affected by low level of demand. Going forward, the pandemic might have a significant negative impact on investment capacity, while the transition to alternative powertrains and the digital transformation of the industry require large investment and restructuring. The long-term impact on CEE economies is highly uncertain, but will depend on the capacity to maintain a comparative advantage, while the sector transforms deeply